The effect of growing system and growing media on the morphological, biological and sensory quality of sweet pepper (Capsicum annuum L.) - Birkás Zita; Balázs Gábor; Füstös Zsuzsanna; Ruszthi Attila; Kókai Zoltán (Journal on Processing and Energy in Agriculture, 2017)
Sweet pepper (Capsicum annuum L.) production is relevant today in Hungary. Due to the importance of the subject, the aim of the study was to evaluate morphological, biological and sensory quality of sweet pepper.The growing experiment was set up at DUNA-R company in Szentes. Three different type of fresh pepper hybrid (Zalkod F1, Gogorez F1, Kapitány F1) were evaluated in unheated plastic house and open field conditions using intensive technology. The fruits were blended and measured with manual digital refractometer (PAL-1, ATAGO). The vitamin C content was determined by the Spanyár-method. Sensory profile analysis was applied with 10 assessors. Based on our results it can be concluded that in forcing the three varieties produced larger fruits in soil culture than in soilless. However in all cases we measured better refraction values in soilless production than in soil culture. Based on the sensory profile analysis the type of growing technology affected mostly morphological parameters.